Transformasi Limbah Pertanian menjadi Bioplastik melalui Teknologi Enzimatik Berbasis Lokal - Rahma Winahyun Jannata; Hukmiyah Aspar (CV. Aksara Global Akademia, 2024)
Agricultural waste is often underutilized, despite its significant potential as a raw material for environmentally friendly products. This study aims to develop bioplastics from corn waste by utilizing locally sourced enzymatic technology as the main catalyst in the biomass conversion process. Corn waste in the form of cobs and post-shelling residues was first prepared through drying, grinding, and mild chemical pretreatment to loosen the lignocellulosic structure. Subsequently, enzymatic hydrolysis was carried out using local enzymes derived from indigenous microorganisms, which decomposed cellulose and hemicellulose into monomeric sugars. The hydrolyzed sugars were then fermented into natural polymers, molded using the solution casting method, and dried to form bioplastic sheets. The results revealed that the produced bioplastics possessed mechanical properties comparable to commercial PLA, with tensile strength of 45–50 MPa, an elastic modulus of 2.5 GPa, and elongation at break of 5–7. Biodegradability testing showed that the material degraded up to ±85 within 90 days, exceeding the minimum threshold of 80% considered satisfactory. These findings confirm that corn waste can be transformed into competitive and eco-friendly bioplastics, while also highlighting the potential of locally based enzymatic technology for industrial-scale applications. The implications of this research extend not only to reducing waste and plastic pollution but also to strengthening the circular economy through the utilization of renewable agricultural resources.